Preliminary Investigation of Bioactive Compounds and Bioautographic Studies of Whole Plant Extract of Euphorbia pulcherrima on Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa. (21st January 2015) - Sharif, H. B.; Mukhtar, M. D.; Mustapha, Y.; Lawal, A. O.
Abstract : The aim of this study is to carry out preliminary investigation of bioactive compounds and bioautographic studies of whole plant extract of Euphorbia pulcherrima on Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa . Tukey HSD test of hierarchy for the effect of different solvents crude extract on bacterial isolates indicates the methanol extract as the most bioactive. The Tukey HSD analysis also showed that the bioactivities of the crude extracts of the various parts of Euphorbia pulcherrima were part dependent and the whole plant was the most bioactive. The ethyl acetate fraction of the methanol extract of the whole plant of Euphorbia pulcherrima has been shown in this work to contain phytochemicals which have shown remarkable activities against Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa . The bioactivities against the test organisms were due to the combined effects of the compounds separated on TLC plates. Families of terpenoids, flavonoids, alkaloids, saponin, and steroids that were detected in the extracts were identified by GC-MS. The various classes of phytochemicals in the E. pulcherrima plant provided the antimicrobial potency of the plant.